The Role of Historical Cultural Memory in Uzbek Documentary Cinema - Khaithmatova Sabohat (Researchparks Publishing, 2022)
The article discusses some issues in the development of documentary filmmaking in Uzbekistan. The importance of historical subject as an important component of the historical memory category is highlighted.